Full-lung simulations of mechanically ventilated lungs incorporating recruitment/derecruitment dynamics - Ma, Haoran; Fujioka, Hideki; Halpern, David; Bates, Jason H. T.; Gaver, Donald P. (Frontiers in Network Physiology, 2023)
This study developed and investigated a comprehensive multiscale computational model of a mechanically ventilated ARDS lung to elucidate the underlying mechanisms contributing to the development or prevention of VILI. This model is built upon a healthy lung model that incorporates realistic airway and alveolar geometry, tissue distensibility, and surfactant dynamics. Key features of the ARDS model include recruitment and derecruitment (RD) dynamics, alveolar tissue viscoelasticity, and surfactant deficiency. This model successfully reproduces realistic pressurevolume (PV) behavior, dynamic surface tension, and time-dependent descriptions of RD events as a function of the ventilation scenario.Simulations of Time-Controlled Adaptive Ventilation (TCAV) modes, with short and long durations of exhalation (TLow -and TLow + , respectively), reveal a higher incidence of RD for TLow + despite reduced surface tensions due to interfacial compression. This finding aligns with experimental evidence emphasizing the critical role of timing in protective ventilation strategies. Quantitative analysis of energy dissipation indicates that while alveolar recruitment contributes only a small fraction of total energy dissipation, its spatial concentration and brief duration may significantly contribute to VILI progression due to its focal nature and higher intensity.Leveraging the computational framework, the model may be extended to facilitate the development of personalized protective ventilation strategies to enhance patient outcomes. As such, this computational modeling approach offers valuable insights into the complex dynamics of VILI that may guide the optimization of ventilation strategies in ARDS management.